Combining ability analysis for seed yield and its components in sesame - Hassan, Mohamed Y; Ibrahim, Abu Elhassan S (Gezira Journal of Agricultural Science, 2014)
Sesame ( Sesamum indicum L.) experiments, were carried out in central Sudan during the rainy season of 2009 at two locations (Abu Naama and Sinnar). The hybridization plan consisted of seven male and seven female parents giving 49 crosses following line x tester arrangement. Treatments were arranged in a randomized complete block design with three replicates. The crosses and their parents were sown on the 7 th of July for all the experiments at both locations. The traits measured were days to 50% flowering, days to maturity, plant height, number of capsules per plant, number of seeds per capsule, capsule length, 1000-seed weight and seed yield. Analysis of variance revealed that genetic variability was highly significant for all the characters studied at both locations and across them. Combining ability analysis showed that additive gene effects were important for inheritance of days to 50% flowering, plant height, number of capsules/plant, number of seeds per capsule, capsule length, 1000-seed weight, days to maturity and seed yield, whereas non-additive gene effects were important for number of seeds/capsule, indicating that the inheritance of this trait is due to specific combining ability (SCA). Combining ability analysis showed that parents, L7, L5, T2, T5 and T6 were good combiners for high seed yield as well as for most of the other traits measured in this study. Assessment of SCA effects for seed yield at Abu-Namma revealed that hybrid T4 x L4 had a maximum positive SCA effect and a high per se performance followed by T2 x L2, T5 x L5 and T6 x L3, while at Sinnar T6 x L6 had the highest positive SCA effects followed by T6 xL3, T1 x L5 and T2 x L6. However T6 x L3, T1 x L5, T4 x L2 and T2 x L1 exhibited the highest SCA effects across sites. The present study suggested hybrids T6 x L3, T1 x L5 and T4 x L2 to be tested in multi-location trials for commercial utilization, while, parents L7, L5, T2 and T6 can be used in recurrent selection.    أجريت هذه التجارب في السودان أثناء الفصل الممطر عام 2009 في أبو نعامة وسنار بإتباع تحليل سلالة x مختبر line x tester analysis)) والذي شمل سبعة آباء ذكورmale parents)) وسبعة أباء اناث  (female parents) معطية 49 هجيناً. أستخدم تصميم القطاعات العشوائية الكاملة بثلاث مكررات. زرعت التجارب في يوم 7 يوليو 2009 في كلا الموقعين. الصفات التي تمت دراستها شملت عدد الأيام حتى 50% إزهار، عدد الأيام حتى النضج، طول النبات، عدد الكبسولات في النبات، عدد البذور في الكبسولة، طول الكبسولة، وزن 1000 بذرة وإنتاجية البذور. أظهر تحليل التباين وجود فروق معنوية لكل الصفات المدروسة في الموقعين. أظهر تحليل القدرة علي التالف أن تأثيرات الفعل الإضافي للجين كانت أهم لتوريث صفات عدد الأيام حتى 50% إزهار، طول النبات، ارتفاع أول كبسولة، ارتفاع أول فرع، عدد الفروع في النبات، عدد الكبسولات في النبات، طول الكبسولة، عدد الأيام حتى النضج، وزن 1000 بذرة و إنتاجية البذور كما كانت تأثيرات الفعل الجيني غير الإضافي مهمة في توريث صفة عدد البذور في الكبسولة وهذه النتيجة تشير بان السيادة وتفاعلات التفوق تتحكم في تلك الصفة. أظهرت تأثيرات القدرة العامة للاتحاد إن الآباء L7  T5, T2, L5,و  T6كانت الأفضل قدرة على الاتحاد لإنتاج البذور بالإضافة لأغلب الصفات الأخرى في التحليل المشترك. الهجن التي أظهرت أعلى قوة  هجين في أبونعامة T5 x L5, T2 x L2, T4 x L4 وT6 x L3 ، بينما في سنار T6 x L6, T6 x L3, T2 x L6 و T1 x L5وعبر الموقعين  T6 x L3, T1 x L5, ,T4xL2 وT2 x L1. وجد أن هناك ارتباطاً موجباً لإنتاجية البذور لكل من وزن 1000 بذرة ، عدد الكبسولات في النبات وعدد الأيام حتى النضج. اقترحت الدراسة الحالية إن الهجنT1 x L5, T6 x L3  وT6 x L7 لإنتاج البذور أما الآباء T4، T1 ، L6و T6  فيمكن استخدامهم في التهجين الرجعى